2024
DOI: 10.1021/acsenergylett.4c00799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cation Disorder on Lithium Transport in Halide Superionic Conductors

Peichen Zhong,
Sunny Gupta,
Bowen Deng
et al.

Abstract: Li 2 ZrCl 6 (LZC) is a promising solid-state electrolyte due to its affordability, moisture stability, and high ionic conductivity. We computationally investigate the role of cation disorder in LZC and its effect on Li-ion transport by integrating thermodynamic and kinetic modeling. The results demonstrate that fast Li-ion conductivity requires Li-vacancy disorder, which is dependent on the degree of Zr disorder. The high temperature required to form equilibrium Zr disorder precludes any equilibrium synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…This explains the differences in the performance of Li 3 YCl 6 synthesized under different experimental conditions. Other potential strategies include aliovalent doping and lithium stoichiometry change, which can lead to frustration in lithium sublattice to break the ordering tendency. , Our research reveals the ion diffusion characteristics in anisotropic materials and provides practical engineering strategies to further optimize the ion conductivity of the material at room temperature, thereby providing guidance for designing high-performance solid-state electrolyte materials.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This explains the differences in the performance of Li 3 YCl 6 synthesized under different experimental conditions. Other potential strategies include aliovalent doping and lithium stoichiometry change, which can lead to frustration in lithium sublattice to break the ordering tendency. , Our research reveals the ion diffusion characteristics in anisotropic materials and provides practical engineering strategies to further optimize the ion conductivity of the material at room temperature, thereby providing guidance for designing high-performance solid-state electrolyte materials.…”
Section: Discussionsupporting
confidence: 83%
“…Besides anion packing, cation arrangement is another crucial factor that dictates the lithium diffusion mechanism. Wang et al used ab initio molecular dynamics (MD) simulations to study the effect of Y/Li antisite defects in Li 3 YCl 6 , which are also a kind of cation disordering, and concluded that these antisite defects might be detrimental to lithium diffusion due to the channel-blocking effect . Later, they performed MD simulations with a machine learning force field and found that the mobile Li sublattice goes through a superionic transition at 425 K, with a drastic increase of activation energy under lower temperature .…”
Section: Introductionmentioning
confidence: 99%